Characteristics of Students’ Cognitive Ability on the Hyperopia Concept: Rasch Analysis - Isnaini Agus Setiono; Anggraining Widiningtyas (Berkala Ilmiah Pendidikan Fisika, 2023)
Knowing the characteristics of students' cognitive abilities is very useful for designing appropriate learning so that students can achieve holistic cognitive abilities. This study aimed to analyze the characteristics of students' cognitive abilities on the hyperopia concept. Rasch analysis includes person and item analysis, which is used to analyze the characteristics of students' cognitive abilities. The research subjects were 64 K-10 students consisting of 38 female students and 26 male students at a public high school in West Bandung Regency. The instrument used to identify students' cognitive abilities on the hyperopia concept is an essay test consisting of 6 items from levels C1-C6 according to the revised Bloom's taxonomy. The results show that the student's cognitive abilities at the level of remembering (100%), understanding (94%), and applying (91%) are in the very good category. Meanwhile, the cognitive abilities at the analyzing, evaluating, and creating levels were below the average cognitive abilities of the students (logit value 0.79). The cognitive ability of female students at the analyzing level is significantly higher than that of male students. The results of this study can be used as an assessment to develop learning activities.